Novel Nanoliposomes Alleviate Contrast-Induced Nephropathy by Mediating Apoptosis Response in New Zealand Rabbits - Zhang, Peng; Zhang, Xue; Zhang, Jing; Song, Yanqiu; Liu, Ting; Zeng, Zhican; Fu, Xiaofeng; Fu, Han; Zhang, Hong; Qin, Qin; Fu, Naikuan; Guo, Zhigang (Frontiers in Molecular Biosciences, 2021)
The aim of this study was to test the preventive effects of nanoliposomes against contrast-induced nephropathy (CIN) in New Zealand rabbits. Sixty New Zealand rabbits were randomly divided into four groups, with 15 rabbits in each group: control group, contrast group, hydration group and nanoliposome group. Scr and BUN were measured before and after injection of the contrast agent iopromide. Oxidative stress markers, such as superoxide dismutase (SOD) and malondialdehyde (MDA), and apoptosis markers, such as Bax and Bcl-2, were measured by enzyme-linked immunosorbent assay (ELISA). Rabbits were killed 24 hours after injection of the contrast medium and both kidneys were removed. Real time PCR (RT-PCR) and Western blot assays were performed in kidney tissue. Pathological changes were analyzed under the optical and electron microscope. Compared with the hydration group, the nanoliposome group showed improved protection of renal function, with significantly different Scr and BUN levels, incidence of CIN, apoptosis index, RT-PCR and Western blot protein expression patterns. Under the optical and electron microscope, the renal injury in the nanoliposome group was less than in the hydration group. However, based on SOD and MDA, there was no significant difference in oxidative stress when compared with the hydration group. Apoptosis is an important mechanism in CIN. Nanoliposomes can prevent the occurrence of CIN by decreasing apoptosis, reducing damage to the kidney by the contrast agent.